2006
DOI: 10.1111/j.1460-9568.2006.05159.x
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between the perifornical hypothalamic area and oral pontine reticular nucleus in the rat. Possible implication of the hypocretinergic projection in the control of rapid eye movement sleep

Abstract: The perifornical (PeF) area in the posterior lateral hypothalamus has been implicated in several physiological functions including the regulation of sleep-wakefulness. Some PeF neurons, which contain hypocretin, have been suggested to play an important role in sleep-wake regulation. The aim of the present study was to examine the effect of the PeF area and hypocretin on the electrophysiological activity of neurons of the oral pontine reticular nucleus (PnO), which is an important structure in the generation an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
30
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 58 publications
(62 reference statements)
7
30
0
Order By: Relevance
“…Considered with data showing that delivering hypocretin-1 to the PnO increases GABA levels in the PnO 13 and causes inhibition of some PnO neurons, 10 and with evidence that GABAergic transmission in the PnO is wakefulness promoting, 13,[19][20][21][22][23][24][25] the present results support the interpretation that increasing GABAergic transmission in the PnO is one mechanism by which hypocretin-1 increases wakefulness. The results are discussed below relative to the functional roles of hypocretin-1 in rat PnO and the mechanisms by which hypocretin-1 administered to the PnO causes an increase in wakefulness.…”
Section: Rat 3 Rat 4 Time Post-injection (H)supporting
confidence: 76%
See 3 more Smart Citations
“…Considered with data showing that delivering hypocretin-1 to the PnO increases GABA levels in the PnO 13 and causes inhibition of some PnO neurons, 10 and with evidence that GABAergic transmission in the PnO is wakefulness promoting, 13,[19][20][21][22][23][24][25] the present results support the interpretation that increasing GABAergic transmission in the PnO is one mechanism by which hypocretin-1 increases wakefulness. The results are discussed below relative to the functional roles of hypocretin-1 in rat PnO and the mechanisms by which hypocretin-1 administered to the PnO causes an increase in wakefulness.…”
Section: Rat 3 Rat 4 Time Post-injection (H)supporting
confidence: 76%
“…Extracellular recording studies of PnO neurons in urethane-anesthetized rat show that iontophoretic application of hypocretin-1 causes a hyperpolarization that is blocked by prior application of bicuculline. 10 This finding indicates that the hypocretin-1-induced inhibition of PnO neurons is mediated by GABA A receptors. Identified GABAergic neurons in brainstem slices of mouse PnO have been shown to be excited by hypocretin-1, 18 and intracellular recording studies in halothane-anesthetized cat show that hypocretin-1 can also cause direct depolarization of PnO neurons and an increase in PnO neuronal firing rate.…”
Section: The Neuropeptides Hypocretin-1 and Hypo-cretin-2 (Orexin A Amentioning
confidence: 70%
See 2 more Smart Citations
“…With the assumption that OX2 receptors are coupled exclusively to G q proteins, a disinhibitory action through their presynaptic regulation of inhibitory GABAergic neurons might be a probable mechanism (Kukkonen et al, 2002). Studies have also suggested an excitatory role of OX2 receptors in modulating activity of GABAergic neurons in the medial septum/diagonal band of Broca (Wu et al, 2002) and arcuate nucleus (Burdakov et al, 2003), indicating that, at least in other brain areas, activation of OX2 receptors could result in an increase of GABA release and a subsequent inhibitory action on other neurotransmitters in the area via GABA A receptors (Nuñez et al, 2006;Brevig et al, 2010). An alternative mechanism could involve a direct action through OX2 receptors coupled to G i/o proteins and localized on cholinergic, histaminergic, and norepinephrinergic nerve terminals.…”
Section: Discussionmentioning
confidence: 96%